Evaluation of Universiti Malaysia Pahang Online Resources Access with Mobile Technology Towards Strategic Knowledge Management - Aziman, Abdullah; Rahmah, Mokhtar; Amelia, Hasan (Penerbit UMP, 2015)
In knowledge-based economy, the role of institute of the higher education is very important in shaping the future landscape of a country not only to supply the human capital but also to prepare the people to venture into a changing world economy. Therefore, the function of the related department such as the library in which responsible to manage the knowledge of the institution also becomes more challenging than before. Mobile technology, smart phone in particular, is very useful device not only to access information but it also able to create a new information. This information can be regard as a new knowledge as well. The purpose of our study is to evaluate the Universiti Malaysia Pahang library readiness for implementation of mobile technology such as smart phone and tablet towards strategic knowledge management. We analyzed the data based on the online tracking services provided by Google Analytics services that has been embedded in the two websites that offering the users to access the online materials. The scope of observed data is for four years only, 2011 until 2014. We found that there are more than 248 different devices been used to access the online resources representing 2.13% of overall sessions or typical access through desktop web browsers. The time series analysis using central moving average on segmented quarterly for four years data shows there is a linear incremental pattern of user access by mobile technology. We predict based on the four years data using linear regression analysis. The result shows 35% of incremental is expected for the next year 2015. To conclude, it is very crucial for the library management to consider of taking advantage of the mobile technology particularly smart phone users towards strategic knowledge management.